Selective targeting of genes regulated by zinc finger proteins in endometriosis and endometrioid adenocarcinoma by zinc niflumato complex with neocuproine - Ivana Špaková; Lukáš Smolko; Gabriela Sabolová; Zuzana Badovská; Katarína Kalinová; Corina Madreiter-Sokolowski; Wolfgang F. Graier; Mária Mareková; Janka Vašková; Miroslava Rabajdová (Scientific Reports)
Abstract Inadequate angiogenesis of endometriotic implants stimulated by the inflammatory microenvironment in the uterine region leads to the development of gynecological diseases, which significantly reduce the fertility and vitality of young women. Angiogenic processes are controlled by factors whose activities are regulated at the gene level by reactive oxygen species (ROS), hypoxia-induced factors (HIFs), and zinc-finger proteins (ZnFs) or posttranscriptionally via non-coding RNAs. The cooperation of these factors is responsible for the manifestation of pathological stimuli in the form of endometriosis of the body of the uterus, ovaries, or peritoneum, from which endometrioid carcinoma can develop. Molecules that can control gene expression by their intercalation to target DNA sequence, such as [Zn(neo)(nif)2], could prevent the hyperactivation of pro-angiogenic pathways (decrease HIF-1α, VEGF-A, TGF-β1, COX2, and ANG2/ANG1), reduce the formation of ROS, and reduce the risk of uterine neoplasticity. The NSAID-metal complex [Zn(neo)(nif)2] shows an ability to intercalate into ZNF3-7 target DNA sequence at a higher rate, which could explain its effect on genes regulated by this transcription factor. In addition, [Zn(neo)(nif)2] affects ROS production and Ca2+ level, possibly pointing to mitochondrial dysfunction as a potential cause for the described apoptosis.